As adaptações razoáveis no modelo de educação inclusiva para estudantes surdos - Ferreira, Rebeca Costa Gadelha da Silveira Lopes (2019)
The UN International Convention on the Rights of Persons with Disabilities has launched a new paradigm about the conquest and protection of the rights of persons with disabilities, in order to afirm, according to Rafael de Assís Roig, the existence of a scenario before and after the creation and adoption of this international law. There is no doubt that many paradigms have been substituted in order to understand the problematic involving persons with disabilities as an issue of human and fundamental rights, which is inspired by the human rights model, in accordance to Theresia Degener. The present research seeks to analyze the mechanism of reasonable accommodations, as proposed by the CRPCD and its compatibility with the Brazilian Inclusion Law, intending to investigate its theoretical and conceptual application in order to promote the right to education of deaf students, under the bias of the inclusion paradigm. To do so, some goals will be outlined throughout the chapters to discuss the thematic and problem of inclusive education for deaf students and reasonable accommodation. It is intended, firstly, to indicate which elements encompass reasonable accomodations and, therefore, to determine how the hermeneutical procedure for the application of this instrument would be given. Secondly, after the theoretical-conceptual development of the accommodations, it aims to analyze how and to what extent they could be used to improve the inclusive education of deaf students, pointing out examples of their application in the context of the teaching and learning process, especially when it is necessary and requested by the student to enable his / her full participation in education (to understand what is being taught) and school (to participate with other students on equal opportunities). In this sense, it is proposed to develop a conceptual and introductory framework for the application of reasonable accommodations, according to the international theorists' view, adapting these concepts seized to the brazilian cultural, social and political context. This research was structured according to the methodological bases of the theoretical, descriptive, bibliographic, documentary, qualitative exploratory research, with the presentation of three chapters. The first one will discuss the non-linear evolution of disability models, according to the bibliographic production of Agustina Palácios, Rafael de Asís Roig and Theresia Degener. The second chapter will explore reasonable accomodations, especially its concept and interpretative elements in order to enable the development of the step by step for its application, in accordance to Rafael de Asís Roig. Thus, the aim is to improve the accommodation to enable deaf students to access education in the light of the inclusion paradigm, when it is verified that accessibility and universal design can not justifiably be applied. The third and final chapter will present, in a conceptual and theoretical way, the application of reasonable accommodations in the education of the deaf included in the regular education through inclusive practices which are sensitive to the complexity of the deaf community. Finally, it should be pointed out that the theme presented in this research must be discussed, since it is part of a whole movement of struggles, resistance, recognition and protection of the rights of deaf students in the affirmation of "being deaf "inserted in a community, culture and identity of their own.